2014
DOI: 10.1115/1.4026546
|View full text |Cite
|
Sign up to set email alerts
|

Laser Induced Chemical Deposition of Ferrihydrite Nanotubes: Exploring Growth Rate and Crystal Structure

Abstract: This paper is one of three papers exploring and confirming a novel high rate nanomanufacturing method using laser to induce and accelerate chemical synthesis and deposition of nanotubes. We have shown elsewhere that the growth rate of SnO 2 nanotubes by this method is a few orders faster than that by the state of the art electrochemical deposition method, the growth rate of the nanotubes is favorably affected by increasing the laser power under a constant number of scanning passes, and the process can grow nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous studies showed that it was feasible for a great variety of nanomaterials to be produced efficiently through solution-based reactions. SnO 2 , Fe 3 O 4 , MnO 2 , ZnS, etc., were successfully deposited by a pulsed-laser method in previous studies. Conventional nanomaterial synthesis methods, such as chemical vapor deposition or hydrothermal reaction, usually show a low growth rate. For example, the typical growth rate of ZnO in a hydrothermal process is in the range of a few hundred nanometers per hour. The growth rate in vapor depositions could reach a few nanometers per second, but it usually requires high temperature which demands a well-controlled environment that is not always compatible with other nanofabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that it was feasible for a great variety of nanomaterials to be produced efficiently through solution-based reactions. SnO 2 , Fe 3 O 4 , MnO 2 , ZnS, etc., were successfully deposited by a pulsed-laser method in previous studies. Conventional nanomaterial synthesis methods, such as chemical vapor deposition or hydrothermal reaction, usually show a low growth rate. For example, the typical growth rate of ZnO in a hydrothermal process is in the range of a few hundred nanometers per hour. The growth rate in vapor depositions could reach a few nanometers per second, but it usually requires high temperature which demands a well-controlled environment that is not always compatible with other nanofabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the output of regression analysis, the fitted lines with least sum of square for models 1 and 2 are shown in Eqs. (9) and (10). Different from sample 1, the R square improves from 0.9936 to 0.9940 when adding coating thickness as explanatory variable.…”
Section: Regression Model For Nano-indentation Test Based On Figs 5mentioning
confidence: 83%
“…Such advantages make the laser-induced chemical solution synthesis attractive and environmentally friendly. This innovative process [7,8] is scalable [9], generic [10], and capable of producing a significant improvement in the material performance [11]. It can greatly aid the development of nanostructured materials for a myriad of applications [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new manufacturing method induced by pulsed lasers showed promising capabilities in chemical deposition in solutions, and a wide range of nanomaterials and structures were deposited with high productivity [1][2][3][4][5][6]. Conventionally, the solution based crystallization processes are studied or regarded as equilibrium in isothermal conditions [7,8], where the effect of temperature (T) is generally evaluated in terms of k B T, where k B is Boltzmann constant.…”
Section: Introductionmentioning
confidence: 99%